Thiosteranes in samples impacted by fecal materials and their potential use as marker of sewage input. (January 2015) - Biache, Coralie; Navarro Frómeta, Amado Enrique; Czechowski, Franciszek; Lu, Yueming; Philp, R.Paul
Abstract: Sewage impacted soil, sludge and water samples were studied to understand the occurrence and formation of thiosteranes and to determine the relevance of these compounds as tracers for sewage input into the environment. Soils were collected from wastewater irrigation fields (Wroclaw, Poland), water from the Nexapa River Basin (Mexico), which also received wastewater and wastewater treatment plant (WWTP) effluent, and water and sludge from the Norman WWTP (USA) at different treatment stages. Thiosteranes represented a high proportion of the steroid fraction in the Wroclaw irrigation field and the Nexapa River Basin samples. Small amounts of thiosteranes were found in anaerobically digested sludge from the Norman WWTP. A good correlation between coprostanone and thiosterane concentrations suggests thiosteranes were produced by stanone sulphurization under anoxic conditions. Thiosterane stability under anoxic and suboxic conditions indicates their potential use as tracers for environmental input of sewage products or land application of sewage sludge. Highlights: Thiosteranes can be used as tracers for sewage/wastewater impacted environments. Thiosteranes were found in samples from wastewater impacted environments. Thiol groups of the macromolecular network react with stanones to form thiosteranes. Thiosteranes formed under anoxic conditions are quite stable under suboxic ones. Abstract : "Thiosteranes are formed under weakly acidic and anoxic conditions and appear stable under oxic environments suggesting they can be use as additional tracers for sewage input".